Influence of Temperature and CO2 On Plasma‐membrane Permeability to CO2 and HCO3− in the Marine Haptophytes Emiliania huxleyi and Calcidiscus leptoporus (Prymnesiophyceae). Issue 5 (15th June 2020) - Blanco‐Ameijeiras, Sonia; Stoll, Heather M.; Zhang, Hongrui; Hopkinson, Brian M.
Abstract : Membrane permeabilities to CO2 and HCO3 − constrain the function of CO2 concentrating mechanisms that algae use to supply inorganic carbon for photosynthesis. In diatoms and green algae, plasma membranes are moderately to highly permeable to CO2 but effectively impermeable to HCO3 − . Here, CO2 and HCO3 − membrane permeabilities were measured using an 18 O‐exchange technique on two species of haptophyte algae, Emiliania huxleyi and Calcidiscus leptoporus, which showed that the plasma membranes of these species are also highly permeable to CO2 (0.006–0.02 cm · s −1 ) but minimally permeable to HCO3 − . Increased temperature and CO2 generally increased CO2 membrane permeabilities in both species, possibly due to changes in lipid composition or CO2 channel proteins. Changes in CO2 membrane permeabilities showed no association with the density of calcium carbonate coccoliths surrounding the cell, which could potentially impede passage of compounds. Haptophyte plasma‐membrane permeabilities to CO2 were somewhat lower than those of diatoms but generally higher than membrane permeabilities of green algae. One caveat of these measurements is that the model used to interpret 18 O‐exchange data assumes that carbonic anhydrase, which catalyzes 18 O‐exchange, is homogeneously distributed in the cell. The implications of this assumption were tested using a two‐compartment model with an inhomogeneous distribution of carbonic anhydrase to simulate 18 O‐exchange data and then inferring plasma‐membrane CO2 permeabilities from the simulated data. This analysis showed that the inferred plasma‐membrane CO2 permeabilities are minimal estimates but should be quite accurate under most conditions.